Restricted diffusion of calretinin in cerebellar granule cell dendrites implies Ca2+‐dependent interactions via its EF‐hand 5 domain. (3rd July 2013) - Arendt, Oliver; Schwaller, Beat; Brown, Edward B.; Eilers, Jens; Schmidt, Hartmut
Key points:   The dynamics of the second messenger Ca 2+ are tightly controlled by Ca 2+ ‐binding proteins (CaBPs).   The diffusional mobility of a given CaBP, such as calretinin (CR), defines how it affects the range‐of‐action of Ca 2+ but, if unexpectedly low, may also indicate that the CaBP acts as a Ca 2+ sensor, undergoing specific protein interactions.   Here we quantified the diffusional mobility of CR in dendrites of cerebellar granule cells using microscopic methods.   We find that CR diffuses unexpectedly slow, that its mobility is further reduced when Ca 2+ levels are elevated and that a distinct region of CR interacts with specific targets in a Ca 2+ ‐dependent manner.   Our findings indicate a new 'sensor' role for CR, which may allow for Ca 2+ ‐dependent feedback control of neuronal excitability. Abstract  Ca 2+ ‐binding proteins (CaBPs) are important regulators of neuronal Ca 2+ signalling, acting either as buffers that shape Ca 2+ transients and Ca 2+ diffusion and/or as Ca 2+ sensors. The diffusional mobility represents a crucial functional parameter of CaBPs, describing their range‐of‐action and possible interactions with binding partners. Calretinin (CR) is a CaBP widely expressed in the nervous system with strong expression in cerebellar granule cells. It is involved in regulating excitability and synaptic transmission of granule cells, and its absence leads to impaired motor control. We quantified the diffusional mobility of dye‐labelled CR in mouse granule cells using two‐photon fluorescence recovery after photobleaching. We found that movement of macromolecules in granule cell dendrites was not well described by free Brownian diffusion and that CR diffused unexpectedly slow compared to fluorescein dextrans of comparable size. During bursts of action potentials, which were associated with dendritic Ca 2+ transients, the mobility of CR was further reduced. Diffusion was significantly accelerated by a peptide embracing EF‐hand 5 of CR. Our results suggest long‐lasting, Ca 2+ ‐dependent interactions of CR with large and/or immobile binding partners. These interactions render CR a poorly mobile Ca 2+ buffer and point towards a Ca 2+ sensor function of CR.